2016
DOI: 10.1016/j.jns.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Stroke survivors in low- and middle-income countries: A meta-analysis of prevalence and secular trends

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 55 publications
(64 reference statements)
4
49
0
1
Order By: Relevance
“…2). This is comparable to other studies carried out in Nigeria [4], [8], [9], [10], [11], [12] and [13] and in other LMICs as shown in the reviewed literature evidence [2], [6] and [7]. The only important difference is that most studies in upper-middle-income countries were sampled from urban rather than rural settings like the current study and from an area with high life expectancy (aging population) driven by high standard of living and quality…”
Section: Comparison With Other Studiessupporting
confidence: 89%
See 4 more Smart Citations
“…2). This is comparable to other studies carried out in Nigeria [4], [8], [9], [10], [11], [12] and [13] and in other LMICs as shown in the reviewed literature evidence [2], [6] and [7]. The only important difference is that most studies in upper-middle-income countries were sampled from urban rather than rural settings like the current study and from an area with high life expectancy (aging population) driven by high standard of living and quality…”
Section: Comparison With Other Studiessupporting
confidence: 89%
“…The fact that the result from this current study was comparable with the current estimates reported in most LMICs particularly in Latin America, South East Asia, Europe and Central Asia [2] further underpins the size of the problem in relation to the associated socioeconomic burden among the population in the rural Niger Delta in Nigeria.…”
Section: Comparison With Other Studiessupporting
confidence: 83%
See 3 more Smart Citations